ANALISIS PROGRAM CSR REVITALISASI TAMAN HUTAN KOTA CADIKA DALAM PERSPEKTIF PEMBERDAYAAN EKONOMI PELAKU UMKM DI SEKITAR KAWASAN - Waruwu, Oktavianus; Manalu, Dimpos; Lumbantobing, Artha (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to analyze the implementation of the Corporate Social Responsibility (CSR) Program for the Revitalization of Cadika City Forest Park carried out by PT Tor Ganda from the perspective of economic empowerment of Micro, Small, and Medium Enterprises (MSMEs) around the park area. This study uses a qualitative approach with in-depth interviews with four informants: community leaders around the park, the sub-district, MSMEs, and park maintainers. Data are analyzed narratively to understand community and government perceptions regarding the impact of park revitalization on business capacity, income, and MSME sustainability. The research results show that before the revitalization, Cadika City Forest Park was poorly maintained, with damaged facilities, minimal lighting, and low visitor numbers, which impacted on limited MSME income. After the revitalization, the park became more organized, clean, and safe, with a jogging track, children's play area, park benches, and adequate lighting. The increase in public visits directly increased the business capacity, income, and sustainability prospects of MSMEs. Traders were able to increase capital, expand the variety of merchandise, improve business facilities, and recruit additional staff. From the perspective of the sub-district government, this CSR program aligns with the regional development vision, creating a mutually supportive local economic ecosystem and strengthening social cohesion. This analysis shows that CSR not only serves to beautify public spaces but also serves as a strategic instrument for local economic empowerment, supporting the sustainable growth of small businesses. This study recommends regular park maintenance and mentoring MSMEs through management training, product innovation, and access to capital to ensure long-term sustainability of CSR benefits. These findings contribute to the development of CSR theory in the context of sustainable development and community economic empowerment.